How far do you want to go? : lessons from a common sense billionaire - Catsimatidis, John, 1948- (Ascent Audio, 2023)
Born on the small Greek island of Nisyros, John Catsimatidis immigrated to the States with his family and quickly became a true New Yorker, raised in Harlem. He went to school by day and worked in a small grocery store by night to help his parents pay the bills until, just eight credits short of graduating from New York University, he opted to work in the grocery business full-time. Today, that grocery business has become the Red Apple Group, a conglomerate with interests in energy, real estate, aviation, baseball, entertainment, and media, including the iconic radio station WABC, where John hosts leading figures in government, politics, business, and economics. As Catsimatidis has discovered, the American Dream doesn't come with an instruction manual-or even a sign to let you know when you've arrived at the finish line. How Far Do You Want to Go? tells Catsimatidis's dynamic story, from his beginnings in the grocery business to entering the political arena, including a New York City mayoral campaign. He's tried his hand at nearly everything, but he's far from finished with his adventures. Now, he offers listeners a glimpse into the wisdom he's gained-and the excitement he has for what the future holds in store.